2011
DOI: 10.1037/a0021284
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of biliteracy development in children in French immersion: A 4-year longitudinal study.

Abstract: English language predictors of English and French reading development were investigated in a group of 140 children who were enrolled in French immersion programs. Children were first tested in kindergarten, and their reading achievement was tested yearly in both English and French from Grades 1 to 3, with word-level and passage-level measures that assessed accuracy as well as fluency. Hierarchical linear modeling was used to examine which English variables predicted Grade 3 outcomes and growth rates in English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 73 publications
6
53
0
Order By: Relevance
“…Nonsense word reading had little statistical significance in predicting future L2 reading fluency, accuracy, or comprehension. This particular finding, which Bourgoin noted concurs with that of Jared et al (2011), relates to several features of the study that sets it apart. Unlike previous studies of relationships between L1 and L2 literacy indicators, Bourgoin's investigation presents a vision of reading ability that goes beyond the decoding of nonsense words and graded wordlists, by examining the learners' ability to create meaning from text.…”
Section: Provision Of Support In French Immersionsupporting
confidence: 51%
“…Nonsense word reading had little statistical significance in predicting future L2 reading fluency, accuracy, or comprehension. This particular finding, which Bourgoin noted concurs with that of Jared et al (2011), relates to several features of the study that sets it apart. Unlike previous studies of relationships between L1 and L2 literacy indicators, Bourgoin's investigation presents a vision of reading ability that goes beyond the decoding of nonsense words and graded wordlists, by examining the learners' ability to create meaning from text.…”
Section: Provision Of Support In French Immersionsupporting
confidence: 51%
“…Recent studies examining the possibility of using L1 early literacy predictors to predict future L2 reading achievement have found evidence that English measures of phonological awareness correlated positively with L2 word reading (Comeau et al, 1999;Durgunoglu, Nagy, & Hancin-Bhatt, 1993;Erdos et al, 2011;Tingley et al, 2004). There is also evidence that phonological measures and other L2 early literacy indicators such as the knowledge of letters can be used to predict future L2 word reading and comprehension ability Haigh et al, 2011;Jared, Cormier, Levy, & Wade-Woolley, 2011). Moreover, studies have found that L1 phonological awareness and phonological access (rapid automatized naming of letters) can be used to distinguish between strong and at-risk L2 readers (MacCoubrey et al, 2004;Erdos et al, 2013) and thus could be used to identify L2 students who might be at risk for reading difficulties.…”
Section: The Role Of L1 Predictors In Assessing L2 Readersmentioning
confidence: 96%
“…Clearly, other measures of Spanish abilities, such as working memory, rapid auditory naming, spelling, and text-reading fluency, would yield additional data for consideration (Jared et al, 2011).…”
Section: Limitationsmentioning
confidence: 99%
“…The NNAT has been used in previous research with young second-language learners (Jared, Cormier, Levy, & Wade-Woolley, 2011). The NNAT is composed of common shapes and designs and required the child to select one of five choices to complete a given shape or pattern.…”
Section: Sample Selection Processmentioning
confidence: 99%
See 1 more Smart Citation